Ibn al-Khatib and his theory of contagion - Senan, Shayma; Othman, Raihan (IIUM Press, 2011)
The main focus of this chapter is to answer who is the first scientist discovered and described the theory of contagion. In addition, the significant of this chapter is to evaluate Ibn AI-Khatib's contributions to the progress of medicine. The method used in this chapter is as follows: a brief review ofIbn AI-Khatib's life is given, as well as a description on his theory of contagion and what was the belief on his time about diseases.The last of the great Andalusian physicians was Ibn aI-Khatib, who was also a noted historian, poet, and statesman. Ibn AI-Khatib played important role in the political and intellectual life of Granada during the 14th century. Ibn aI-Khatib was the last representative of the Andalusian medical tradition (Brockopp and Thomas, 2008, p. 38). Ibn AI-Khatib wrote this plague treatise soon after the initial outbreak of the Black Death in 1349. His work Muqni'at aI-sa'i! 'an al-marad al-ha'i! (the satisfaction of the Questioner Regarding the Appalling Illness) dealt chiefly with the medical aspects of the plague (Phillips, 1998, pp. 47 - 62). Soon after his death, the energies of the Muslims of al-Andalus were wholly absorbed in the long costly struggle against the Christian force (Brockopp and Thomas, 2008, p. 38).